1986
DOI: 10.1055/s-2007-969154
|View full text |Cite
|
Sign up to set email alerts
|

Sarothralen A and B, New Antibiotic Compounds fromHypericum japonicum

Abstract: Two antibiotic compounds, sarothralen A and sarothralen B, from Hypericum japonicum Thunb. ( Sarothra japonica Thunb.) have been isolated and their structures were elucidated on the basis of spectroscopic data. The compounds contain phloroglucinol and filicinic acid residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…(Chinese name, Tianjihuang) has been used as a Chinese medicinal herb for the treatment of infectious hepatitis, bacterial diseases and tumors for many years (Hu et al, 1996;Ishiguro et al, 1986;Wu et al, 1998;Li et al, 1993). Previous phytochemical studies of Tianjihuang have demonstrated that it mainly contains flavonoids (Wu et al, 1998;Ishiguro et al, 1991bIshiguro et al, , 1993, phloroglucinol derivatives (Hu et al, 2000), xanthonoids (Ishiguro et al, 1997), chromone glycosides (Wu et al, 1998;Ishiguro et al, 1990) and peptides (Ishiguro et al, 1991a).…”
Section: Introductionmentioning
confidence: 99%
“…(Chinese name, Tianjihuang) has been used as a Chinese medicinal herb for the treatment of infectious hepatitis, bacterial diseases and tumors for many years (Hu et al, 1996;Ishiguro et al, 1986;Wu et al, 1998;Li et al, 1993). Previous phytochemical studies of Tianjihuang have demonstrated that it mainly contains flavonoids (Wu et al, 1998;Ishiguro et al, 1991bIshiguro et al, , 1993, phloroglucinol derivatives (Hu et al, 2000), xanthonoids (Ishiguro et al, 1997), chromone glycosides (Wu et al, 1998;Ishiguro et al, 1990) and peptides (Ishiguro et al, 1991a).…”
Section: Introductionmentioning
confidence: 99%
“…HJT, an annual herb from the genus Hypericum L., known in traditional Chinese medicine as Tian-ji-huang, grows mainly throughout southern China. HJT has been used in a Chinese herbal compound formula for many years for the treatment of bacterial diseases; infectious, acute and chronic hepatitis; gastrointestinal disorder; internal hemorrhage and tumors (13,14). Data in the present study demonstrated that the HJT extract significantly inhibited the growth of H22-transplanted tumors and had a synergistic tumor-inhibiting effect with the 5-FU group.…”
Section: Discussionmentioning
confidence: 47%
“…H. perforatum also displayed anti-immobility effect in the forced swimming test (Butterweck et al, 1997(Butterweck et al, , 1998. The most lipophilic fraction of several species of the genus Hypericum is rich in phloroglucinol derivatives (Ishiguro et al, 1986;Jayasuriya et al, 1991;Rocha et al, 1994Rocha et al, , 1995. Traditionally, the naphthodianthrone, hypericin, was considered to be the most active constituent of H. perforatum, but only few data are still in favour of the hypothesis that the antidepressant activity is due to hypericin only (Wagner and Bladt, 1994;Butterweck et al, 1998).…”
Section: Resultsmentioning
confidence: 99%